A short review on diamond reinforced aluminium composites - Kusuadi, Nur Izzah Nazurah; Jamal, Nur Ayuni; Ahmad Nor, Yusilawati (Springer, 2023)
Diamond, which is a type of carbon material, is an attractive reinforcement material for aluminium matrix composites due to its excellent properties such as high hardness, high thermal conductivity and low coefficient of thermal expansion. Diamond reinforced aluminium (diamond/Al) composite is a promising candidate material for applications of thermal management and electronic packaging. However, there are some major issues between Al metal matrix and diamond reinforcement that limit the utilization of the composites such as poor wettability and low interfacial bonding. This review discusses the challenges in diamond/Al composites, initiatives taken to solve the issues and processing techniques used to fabricate diamond/Al composites along with related advantages and limitations.